AN ANALYSIS OF JARGONS USED BY THE HUMAN RESOURCES DEPARTMENT AT THE LOVINA BALI - P.D. Marantika; I.G. Budasi; N.K. Wedhanti (Universitas Pendidikan Ganesha, 2020)
argon is one of language varieties that is used based on some purposes. The languagevariety which is called jargon that is used in occupational or used for spesific purposes like in HRD(Human Resource Department) in five stars hotel, especially one of the hotel is The Lovina Bali whichlocated at Lovina, Singaraja north Bali. This study aimed at desacribing (1) the Jargons that are usedin the HRD at The Lovina Bali, (2) the forms of Jargons used among the HRD at The Lovina Bali, (3)the meaning of jargons used among the HRD at The Lovina Bali. The obtain data were indentify using3 instruments : (1) Checklist, (2) Interview Guide and (3) Tape Recording. This study conclude that :(1) There were 121 jargons used in Human Resource Department (HRD).